EVALUATION OF SOME MINERALS AND VITAMINS IN CORD BLOOD FROM RURAL AND URBAN POPULATION OF UDAIPUR REGION - JAIN, SUMAN; BANSAL, PRERNA; PRAJAPAT, RAJNEESH; JADEJA, HARSHDEEP (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Vitamins and minerals collectively referred to as micronutrients have important influence on the health of pregnant women and the growing fetus. Pregnancy is related to increase demand of all nutrients and deficiency any of these can affect pregnancy, delivery, and outcome of pregnancy. Disorders in mineral element nutrition and metabolism can lead to wide variety of malformations. Data on mineral values in newborn are very less in contrast to adult. The present study was planned to analyze some of minerals in the umbilical cord blood of rural and urban population and compare them gender wise. Methods: Our study group consisted of 640 healthy term newborn. The cord blood was collected immediately after a normal delivery. The blood was tested to determine calcium (Ca), magnesium (Mg), Phosphorus (P), Iron (Fe), Vitamins D3, and Vitamin B12. Results: The results showed that the levels of Ca, Mg, P and Fe, Vitamin D3, and Vitamin B12 were higher in urban population than rural ones. All were statistically significant. The levels of Mg, P, Fe, and Vitamin B12 were lower in female urban neonates as compared to male urban neonates. All were significant when compared sex wise. The trend was same with increased levels of Mg, P, Fe, and Vitamin B12 in females of rural population than cord blood of male rural neonates. Conclusions: The result showed that rural and urban population also female and male neonates have genetic variation and difference in mineral metabolism.